Peran Pemerintah Daerah dalam Pemenuhan Hak atas Air Berkualitas di Kota Madiun - Wahyuni, Sri (Universitas Sebelas Maret, 2023)
Water is a basic need in human life. The right to water is a basic human right because water is very necessary and a staple of life's welfare. The right to water is not only a matter of quantity but in urban society it has entered the realm of quality. The state is obliged to ensure that the community achieves universal access to clean water and proper sanitation. The right to quality water must be fulfilled, guaranteed and protected. The fulfillment of the right to quality water is not only carried out by the central government but also requires the participation of local governments. This research examines the extent of the role of the local government of Madiun City in fulfilling the right to quality water. The research method used is socio-legal research by collecting direct data on the people of Madiun City. The results of the study show that the local government of Madiun City plays an important role in fulfilling the right to quality water. In addition to ensuring that all local communities in the region have easy access to quality water, local governments also carry out monitoring of the quality of water used by the community.